Exploring Ethnophysics in Javanese Gamelan: Bridging Cultural Heritage and STEAM-Based Physics Learning - Saputra, Aji; Sambiri, Usman; Fajrhi, Nur (Universitas Khairun, 2025)
This study aims to explore the ethnophysics characteristics of Javanese gamelan and to analyze how these characteristics can be integrated into STEAM-based physics learning. Specifically, the research seeks to identify the ethnophysics phenomena embedded in gamelan instruments, examine their cultural meanings, and formulate pedagogical implications for culturally responsive science education. Using a qualitative ethnographic design, data were collected through interviews, observations, and documentation involving gamelan craftsmen, pengrawit, and cultural experts. The findings show that instruments such as saron, demung, peking, kenong, gong, and kendang embody fundamental physics principles, including vibration, resonance, frequency, amplitude, and damping, which arise naturally from their material composition, construction processes, and performance techniques. At the same time, these instruments carry symbolic values rooted in Javanese philosophy, representing harmony, balance, collectivism, and spiritual interconnectedness. The combination of scientific and cultural dimensions demonstrates that gamelan can serve as an authentic learning medium that bridges traditional knowledge with modern physics concepts. Pedagogically, integrating ethnophysics into STEAM supports interdisciplinary learning that blends scientific investigation, engineering design, mathematical reasoning, technological tools, and artistic expression. This approach enhances contextual understanding, creativity, inclusivity, and cultural identity. The study proposes the Ethno-STEAM model as an innovative framework for decolonizing science education by positioning cultural heritage as a legitimate source of scientific insight. Overall, the ethnophysics of Javanese gamelan offers a transformative pathway for physics learning that is both scientifically rigorous and culturally grounded.